Monitoring Nitrogen Dioxide (NO2) in Environment of Ukraine based on Satellite Data - Yelistratova, Lesya; Apostolov, Alexander; Khodorovskyi, Artur; Tymchyshyn, Maksym (Geomatics and Environmental Engineering, 2023)
Air pollution (especially near industrial enterprises that are located mainly in densely populated regions) is one of the most significant problems of modern ecology. The purpose of this research is to study nitrogen dioxide air pollution over Ukraine, which has a negative impact on human health. As part of the research over the territory of Ukraine, the real planar distribution of nitrogen dioxide (NO2) as well as its local emissions (which make the main contribution to this distribution) were revealed using the materials of the remote sensing of the Earth from the AURA satellite. The results were calculated for the multi-year period of 2005 through 2021 and separately for 2022, which characterized the full-scale war in Ukraine and which made it possible to identify priority polluters; namely, industrial enterprises (thermal power plants, heavy metallurgy enterprises, etc.). For 17 years, the average value of NO2 was 160.78 · 102 molecules/mm2; in 2022, its concentration decreased to 126.93·109 molecules/mm2. The war manifested itself due to the shutdown of industrial enterprises, which were (and remain) priority polluters in Ukraine (particularly in large cities).